2015
DOI: 10.4103/0970-9290.172049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical evaluation of glycosylated haemoglobin level in healthy and chronic periodontitis patients: A chairside diagnostic method

Abstract: Indians are at a high-risk of developing periodontitis and diabetes. These data suggest a possible link between periodontitis and glycemic control in nondiabetic individuals, periodontal disease may be a potential contributor to the development of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our results are in concordance with previous studies that reported higher mean HbA1c levels in periodontitis patients than in individuals without periodontitis. [ 24 25 26 27 ] A cutoff value of HbA1c ≥5.7% for prediabetes was used in our study. Interestingly, the mean values for HbA1c fell in the prediabetic range for the severe periodontitis group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in concordance with previous studies that reported higher mean HbA1c levels in periodontitis patients than in individuals without periodontitis. [ 24 25 26 27 ] A cutoff value of HbA1c ≥5.7% for prediabetes was used in our study. Interestingly, the mean values for HbA1c fell in the prediabetic range for the severe periodontitis group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 21 22 23 ] Few studies have reported higher glycosylated hemoglobin (HbA1c) levels in periodontitis patients than in individuals with healthy periodontium. [ 24 25 26 27 ] Further, studies have also showed an association between severe periodontitis, insulin resistance, and a dysmetabolic state. [ 28 29 30 ] We hypothesized that severe periodontitis patients who were previously undiagnosed for diabetes mellitus had alterations in glycemia when compared to individuals with healthy periodontium.…”
Section: Introductionmentioning
confidence: 99%
“… 126 , 127 Given that periodontitis leads to subclinical inflammation, 128 many studies have evaluated the role of periodontitis on glycemic levels, as well as on the incidence of type 2 diabetes and diabetes complications. 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 Periodontitis is associated with hemoglobin A1c progression in individuals with diabetes. 137 Additionally, deeper probing depths are more closely associated with increased hemoglobin A1c levels.…”
Section: Diabetesmentioning
confidence: 99%
“…Chronic subclinical inflammation plays a role in the pathogenesis of type 2 diabetes 126,127 . Given that periodontitis leads to subclinical inflammation, 128 many studies have evaluated the role of periodontitis on glycemic levels, as well as on the incidence of type 2 diabetes and diabetes complications 129‐136 . Periodontitis is associated with hemoglobin A1c progression in individuals with diabetes 137 .…”
Section: Diabetesmentioning
confidence: 99%